Integrated Metabolome and Transcriptome Analyses Reveal Dissimilarities in the Anthocyanin Synthesis Pathway Between Different Developmental Leaf Color Transitions in Hopea hainanensis (Dipterocarpaceae) - Huang, Guihua; Liao, Xuezhu; Han, Qiang; Zhou, Zaizhi; Liang, Kunnan; Li, Guangyou; Yang, Guang; Tembrock, Luke R.; Wang, Xianbang; Wu, Zhiqiang (Frontiers in Plant Science, 2022)
Changes in plant leaf color during development are directly related to the accumulation or degradation of certain phytochemicals such as anthocyanins. Since some anthocyanins can be beneficial to human health and provide insights into the biology of leaves, the underlying processes and timing by which plants produce these molecules has been the focus of numerous studies. The tree species Hopea hainanensis generally produces green leaves at all growth stages; however, a few explored individuals have been identified possessing red leaves on the top of the seedlings at a young stage. While the phenomenon of leaf color varying with age has been studied in several species, the underlying mechanisms are largely unknown in H. hainanensis. Using a metabolomics approach, the young red leaves in H. hainanensis were found to contain higher levels of anthocyanins and flavonoids than the young green-leaved individuals. Among anthocyanins, pelargonidin and cyanidin were the most likely candidates contributing to the red color of the young leaves. Transcriptome results indicated the genes related to the production of these anthocyanins were significantly upregulated, leading to greater accumulation of red pigments. Specifically, the expression of several MYB and bHLH genes in young red leaf lines was significantly higher than that in the young green leaf lines, especially HhMYB66, HhMYB91, HhMYB6, and HhbHLH70. As such these four transcription factors are probably the main regulatory genes resulting in young red leaves in H. hainanensis. From these results, comparative analyses with other species can be made to better understand the evolution of pigment biosynthesis and how anthocyanins function in plant metabolism and evolution/adaptation.